Defensive Role of Vitamin E Against Nitrosamine-Induced Harm to Testicular Tissues in Male BALB/C Albino Mice - Atyaf Shakir Ahmed; Nedhal ibrahime lateff (مجلة الانبار للعلوم البيطرية)
Nitrosamines are toxic substances that induce oxidative stress. Oxidative stress results from an imbalance between the formation of free radicals (ROS) and their removal from the body and is a direct or indirect cause of a variety of diseases. The research aimed to assess vitamin E's potential protective role against nitrosamine-induced defects of testicular tissues. A total of forty Albino mice, weighing between 20 To25 grams and aged 25 to 30 weeks, were employed for the study. These mice are divided into five groups, each consisting of eight individuals. The initial group served as control, second group received a daily oral dosage of 0.05 mL/ g body weight of nitrosamine over one month. The third group was orally administered 0.1 mL/g of vitamin E. Groups IV and V were provided with vitamin E doses of 0.1 and 0.2 mL/g body weight orally Daily for a month, followed by a nitrosamine dose of 0.05 mL/g. Post the treatment period, blood samples were obtained, and the testis and epididymis tissues were subjected to examination. The study findings revealed notable alterations, encompassing the inhibition of spermatogenesis, reduction in diameters of seminiferous tubules within the testis and epididymis, as well as epithelial cell thickness. Additionally, severe necrosis and germ cell erosion were observed. In contrast, results from the vitamin E-treated animals exhibited favorable changes in the testicular and epididymis tissues when compared to the nitrosamine-exposed group and the control group. Moreover, histological assessments of animals administered a preventive vitamin E dose (0.2 mL/g) alongside nitrosamine indicated enhanced spermatogenesis, evidenced by augmented seminiferous tubule diameters and increased epithelial cell thickness within the testis and epididymis.